Якість надання послуг як основа конкурентоспроможності готельних підприємств - Тітомир, Людмила Анатоліївна; Тітомир, Л. А.; Данилова, О. І.; Данилова, Олена; Titomyr, Liudmyla A.; Danylova, Olena (My University, 2020)
У статті охарактеризовані актуальні проблеми розвитку готельних підприємств України. Розглянуті особливості надання послуг та зроблено акцент на необхідності підвищення якості обслуговування гостей. Високий рівень комфорту, що задовольняє найрізноманітніші побутові, господарські та культурні запити гостей, повинен забезпечуватися всіма службами готельного підприємства. Автоматизовані системи бронювання номерів, можливість online ознайомитися із комфортністю номерів та їхнім дизайном стали нагальною потребою. Основними шляхами покращення якості послуг є впровадження систем управління клімат-контролем, освітленням, кадрове забезпечення підприємств, залучення широкого спектру додаткових послуг. Для збільшення кількості гостей необхідним є пропонування можливості суміщення ділових поїздок із відпочинком, пропозиції сімейного відпочинку круглий рік та залучення місцевих жителів до більш широкого використання можливостей додаткових послуг готелів, таких як: дитячі кімнати, арт-студії, spa-послуги, оздоровчі процедури, тренажерні зали тощо. Важливим ресурсом для підвищення конкурентоспроможності є створення готельних ланцюгів та більш тісне співробітництво з туроператорами, які останнім часом не є зорієнтованими на український ринок, а більше працюють із закордонними фірмами та готелями. Зменшення кількості великих готельних підприємств і розповсюдження по всій території України ідей концептуальних дизайн-готелів свідчить про вагомі зміни, що стосуються якості та форми надання послуг. Якісне харчування, зручності у гостьових будинках та стилізованих під природний відпочинок готельних підприємствах, впровадження екологічно чистих технологій та відновлювальної енергетики, доброзичлива і ненав’язлива підтримка гостей – основні складники забезпечення задоволеності гостей та гарантія перетворення їх на постійних споживачів послуг.

The article describes actual problems of development of hotel enterprises in Ukraine. The peculiarities of service provision are considered and the emphasis is placed on the need to improve the quality of guest service. The high level of comfort, which satisfies the various household, economic and cultural requests of guests, should be ensured by all services of the hotel enterprise. Automated room reservation systems, the ability to view room comforts and their design on-line have become an urgent need. The main ways to improve the quality of services are the implementation of climate control systems, lighting, human resources for enterprises, and the involvement of a wide range of additional services. In order to attract more guests, it is necessary to offer the possibility of combining business trips with vacations, family vacation offers throughout the year with the possibility to plan a trip in advance at a convenient time and at an affordable price. In addition, it is important to involve locals in making more use of the hotel’s additional services: children’s rooms, art studios, spa services, wellness procedures, gyms, billiards and more. More efficient use of material resources requires the implementation of automated technical equipment control systems for the external and internal operation of the hotel enterprise. It will allow to optimize and simplify work of hotel staff, and also to facilitate access and use of services of hotel directly to guests. An important resource for increasing competitiveness is the creation of hotel chains and closer cooperation with tour operators, which recently are not oriented towards the Ukrainian market, but are working more with foreign companies and hotels. The decrease in the number of large hotel enterprises and dissemination in Ukraine the ideas of conceptual design hotels shows not only the necessity of introducing new management techniques to attract guests, but also more significant changes regarding the quality and form of service delivery. The Implementation of clean technologies and renewable energetic is also attracting more guests. Good nutrition, amenities in guest houses and hotel enterprises that are styled for natural relaxation, friendly and unobtrusive support from guests are the main components of ensuring guest satisfaction and guarantee that they will convert to regular customers.
Тітомир Л. А. Якість надання послуг як основа конкурентоспроможності готельних підприємств [Електроний ресурс] / Л. А. Тітомир, О. І. Данилова // Приазовський економічний вісник.- 2020.- №1(18). - С. 155-160. DOI: https://doi.org/10.32840/2522-4263/2020-1-28
Keywords: якість; готельний бізнес; конкурентоспроможність; комфорт; дизайн; quality; hotel business; competitiveness; comfort; design; control systems; Research Subject Categories::SOCIAL SCIENCES::Business and economics